(untitled) (Journal of the College of Basic Education, 2024)
The importance of the research lies in knowing the effect of using Thelin’s model in learning the handstand skill in artistic gymnastics. The aim of the research was to identify the effect of using Thelin’s model in learning the handstand skill in artistic gymnastics The researchers assumed that there are statistically significant differences between the two research groups in learning the skill of standing on hands in artistic gymnastics. The researchers used the experimental method as it is the most appropriate method for the nature of the research problem. The researchers chose the community of origin in a deliberate manner, represented by the third stage students. Through a lottery, the students of the hall (1-3) were chosen to represent the research sample, as the number of its members reached (30) students who were divided into two groups. Experimental and controlled. The researchers chose the handstand skill. After discussing the results, the researchers concluded that the special exercises prepared and designed according to Thelin’s model by the researchers proved effective for the experimental group sample, with evidence that the experimental group recorded preference over the control group.